2011
DOI: 10.1007/s11060-011-0536-2
|View full text |Cite
|
Sign up to set email alerts
|

Competing for patients: an ethical framework for recruiting patients with brain tumors into clinical trials

Abstract: With more rapid advances in potential treatments for brain tumours, the number of clinical trials for brain tumour patients is rising. In the context of the challenges of recruitment and enrollment of patients with brain tumors, the dichotomy between the paucity of subjects and abundance of clinical trials creates a unique ethical dilemma, whereby a single patient may be eligible for several studies. Here, we identify and present three approaches for recruiting and enrolling patients who may be eligible for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…This gives it an important advantage over competing approaches. Allowing patients or clinicians to choose between trials, as some advocate,2 6 will not address or minimise the problem of competing studies, since patients and clinicians are not responsible for the completion of studies and will (and perhaps should ) base their choice on considerations other than making sure that the institution's prioritised trials recruit enough to complete. Likewise, randomising participants between competing studies (as per ref.…”
Section: Recruitment Competition and The Problem Of Non-completionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gives it an important advantage over competing approaches. Allowing patients or clinicians to choose between trials, as some advocate,2 6 will not address or minimise the problem of competing studies, since patients and clinicians are not responsible for the completion of studies and will (and perhaps should ) base their choice on considerations other than making sure that the institution's prioritised trials recruit enough to complete. Likewise, randomising participants between competing studies (as per ref.…”
Section: Recruitment Competition and The Problem Of Non-completionmentioning
confidence: 99%
“…A second approach denies that there is any obligation to offer potential participants a choice between competing trials and instead leaves the choice up to clinicians , who typically offer trials based on their own estimation of a trial's therapeutic potential or other, more idiosyncratic factors (such as the level of investment of the clinician or department chief in different studies and what they have to gain from prioritising some over others) 2. A third option, motivated by avoiding bias and ensuring scientific integrity, is to employ a randomising procedure to decide which trials to offer individuals, similar to the use of randomisation to allocate participants to different arms within individual studies 4.…”
Section: Introductionmentioning
confidence: 99%
“…This situation where an individual patient could be eligible for enrollment for several trials creates a unique ethical dilemma. [45] The researchers have to choose from one of the three approaches: Full disclosure, paternalistic and random assignment. The researcher taking the full disclosure approach provides information about all ongoing concurrent trials, allowing parents and participants to make the decision regarding the trial to enroll with.…”
Section: Recruitment Issuesmentioning
confidence: 99%
“…This strategy may erode patient autonomy. [45] Pediatric treatment outcome research focusing on the physical and mental health of children living in rural areas is limited, despite the immense need. Challenges to recruitment include researchers being viewed as outsiders by rural community members, population size and density of rural communities, unique aspects of rural culture and higher rates of poverty and lower educational achievement in rural areas.…”
Section: Recruitment Issuesmentioning
confidence: 99%
“…Absent a centralised mechanism between funders to ensure optimal distribution of trials between sites, trials prioritised at the level of funder may still compete with each other for participants at the site level. Indeed, there is ample evidence that intra-institutional competition between trials is a reality, particularly in certain specialisations such as brain tumour and stroke research 7 8. A recent survey, for example, found that 92% of StrokeNet sites have policies in place for determining which trial should be offered to patients who are eligible for more than one study, confirming that competing trials are common in this space and the importance of prioritisation at the institutional level 9.…”
Section: Institutions As a Locus Of Prioritisationmentioning
confidence: 99%